Political Crisis and The Politics of Religious Divisiveness in Nigeria’s Fourth Republic - Oyetunbi, Oluwaseyi; Akinrinde, Olawale Olufemi (Fakultas Hukum Universitas Negeri Semarang, 2021)
The relationship that exists between politics and religion cannot be over-emphasized in Nigeria polity since the evolution of a sustainable democracy which has heightened the relevance of religion in our society. Religion has been identified as one of the factors that have divided the people of Nigeria who are divided already by many phenomena that are of nature. The diversities engineered by cultures, customs, traditions and values are not as potent as religion in dividing the people, ensuing conflict, creating a paradise for favoritism, generating riot and insurgence. Religious leaders have become force to reckon with in the country, many of them become politicians out of the blues because of their influence on the mindset of their members to decide as regard electioneering activities. However, politics needs to be guided by religion ideally, evidently most policies fabricated, go in line with dogmas of either Christianity or Islam before other indexes may follow. People are better divided by religion. This paper focuses on examining the influence of religion on politics in Nigeria’s fourth republic using the Boko-haram insurgence as the major yardstick to establishing the impacts of religion on the divisive Nigeria.